Architectural erosion determination model using approach-based metrics and quality attributes with Structural Equation Modelling - Babbad, Ahmed Omar Salem (2024)
The success or failure of software development and design heavily depends on software architecture, which plays a vital role in various aspects of the development process. It is acknowledged that having the right architecture is crucial for system design and development. However, as systems evolve, software architecture tends to degrade, leading to architectural erosion. Although several studies have explored different approaches to tackle architectural erosion, with metrics being a common solution, there is a significant gap in knowledge on the metrics used to identify architectural erosion and classify adopted approaches. Therefore, this research aims a model that combines approach-based metrics and architectural attributes quality to address the following main aspects: 1) identification of adopted approaches and commonly used metrics practices associated with each approach to identify architectural erosion, 2) identification provides valuable insights and practical guidance for researchers and practitioners in the field.